1995
DOI: 10.1210/mend.9.5.7565807
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three proline-directed phosphorylation sites in the human androgen receptor.

Abstract: Full-length wild type and deletion mutant human androgen receptors (AR) were transiently expressed in monkey kidney COS cells to identify the phosphorylated amino acid residues. Phosphoamino acid analysis indicated serine (Ser) and threonine (Thr) residues as the major sites of phosphorylation. Both NH2- and carboxyl-terminal fragments containing the DNA-binding domain were highly phosphorylated, suggesting the presence of phosphorylation sites throughout the protein. Site-directed mutagenesis of wild type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 31 publications
5
64
0
Order By: Relevance
“…Higher vertebrates gain the ability to regulate the negative charge by phosphorylation. This is also suggested by the human AR phosphorylation site Ser 650 (8,10), which is Asp in lower species. Similarly, the human estrogen receptor-␣ phosphorylation site Ser 118 (67,68) is Asp in the lamprey estrogen receptor (4).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Higher vertebrates gain the ability to regulate the negative charge by phosphorylation. This is also suggested by the human AR phosphorylation site Ser 650 (8,10), which is Asp in lower species. Similarly, the human estrogen receptor-␣ phosphorylation site Ser 118 (67,68) is Asp in the lamprey estrogen receptor (4).…”
Section: Discussionmentioning
confidence: 64%
“…the AR NH 2 -terminal conserved motif; lanes [5][6][7][8][9], and GST-AR-(220 -270m4) (with the L237A/K239M/V241A/V243A mutations; lanes 9 -12). 30% Input (lanes 13-16) represents 30% of total 35 3), and pCMV5-CHIP⌬TPR (lanes 5 and 6).…”
Section: Fig 3 Interaction Of Chip With the Ar Nh 2 -Terminal Consementioning
confidence: 99%
“…Previous studies have shown that AR Ser-81 is phosphorylated in response to androgens (11), but transient transfection studies in AR-negative cell lines indicate that this site is not required for AR transcriptional activity (13). Here we identify cyclindependent kinase 1 (Cdk1, also called Cdc2) as an AR Ser-81 kinase.…”
mentioning
confidence: 78%
“…Ligand binding induced AR phosphorylation at multiple sites (primarily N-terminal Ser͞Pro sites), but the kinases mediating AR phosphorylation and their importance for AR function have not been established (11,13,43,44). Transfected Cdk1 stimulated AR phosphorylation at Ser-81 and increased AR protein expression, whereas Cdk1 inhibitors decreased Ser-81 phosphorylation of the endogenous AR in LNCaP PCa cells and similarly decreased AR protein expression and transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation